2008
DOI: 10.1002/ange.200705936
|View full text |Cite
|
Sign up to set email alerts
|

Metallfreie Umwandlung von Methan und Cycloalkanen in Amine oder Amide mithilfe eines Borylnitrens

Abstract: C‐H‐Insertion: Borylnitrene, die in situ durch Photolyse der Azide erzeugt werden, wandeln durch intermolekulare C‐H‐Insertion nichtaktivierte Alkane in Aminoborane um (siehe Schema), die wiederum in Amine und Amide überführt werden können. Die Borylgruppe erfüllt zwei Zwecke: Sie verwandelt das Nitren in ein hochreaktives BN‐Vinylidenanalogon, und sie lässt sich leicht unter Freisetzung des Produkts wieder abspalten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…The presence and necessity of the carbene in the formation of 6 – 8 suggests that these reactions are catalytic in carbene, and indeed formation is readily accomplished with the use of 2–3 mol % of I t Bu. In these cases, the quantitative formation of the aminoboranes33, 34 is complete within 2 h at 25 °C. Notably, 6–8 are stable in solution under these conditions.…”
Section: Methodsmentioning
confidence: 98%
“…The presence and necessity of the carbene in the formation of 6 – 8 suggests that these reactions are catalytic in carbene, and indeed formation is readily accomplished with the use of 2–3 mol % of I t Bu. In these cases, the quantitative formation of the aminoboranes33, 34 is complete within 2 h at 25 °C. Notably, 6–8 are stable in solution under these conditions.…”
Section: Methodsmentioning
confidence: 98%
“…[76] In an early example, Sander et al showed that the strongly electrophilic carbene difluorovinylidene reacts directly with H 2 in an argon matrix at 20-30 K with practically no activation barrier to yield 1,1-difluoroethene (125; Scheme 46). [77] Formal insertion of examples of monoamino carbenes into the HÀH bond in solution were recently reported by Bertrand et al [35] (Scheme 18). Remotely related Scheme 43.…”
Section: Other Metal-free Catalytic Hydrogenation Reactionsmentioning
confidence: 94%
“…The use of pinacolato‐ligated borenium cations would conceptually enable the single‐step synthesis of pinacol boronate esters. This approach was initially complicated by the instability of PinBCl,41 and then precluded by the failure of [PinB(amine)] + , synthesized from PinBH (amine= N , N ‐dimethylaniline or 2,6‐lutidine), to borylate N , N ‐dimethylaniline and N ‐methylpyrrole 31. This is attributable to the reduced electrophilicity of boron on replacing catechol for the more electron‐donating pinacol.…”
Section: Methodsmentioning
confidence: 99%